The Effectiveness of Domestic and International Exhibitions as Promotional Tools for Fostering MSMEs' Business Growth in Dinas Perdagangan Kota Balikpapan - Muzzayyanah, Farras Athifah; Wediawati, Tuti (TSAQOFAH, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in strengthening regional economic resilience, yet their growth is often hindered by limited market access and promotional constraints. To address these challenges, the Balikpapan City Trade Office has facilitated MSME participation in both domestic and international exhibitions as a promotional strategy to stimulate business development. This study aims to analyze the comparative effectiveness of domestic and international exhibitions in fostering MSME growth in Balikpapan. Using a qualitative descriptive approach, data were collected through semi-structured questionnaires with MSME participants and documentation from the Trade Office, and were analyzed thematically. The findings show that domestic exhibitions generate direct and short-term benefits, including increased sales transactions, acquisition of new local customers, and enhanced national brand visibility. By contrast, international exhibitions provide long-term and strategic impacts by expanding global business networks, elevating brand credibility, and opening opportunities for export, although their outcomes require higher levels of legal, certification, and production readiness. Overall, the results suggest that domestic and international exhibitions function not as substitutes but as complementary promotional tools within a progressive business development pathway, and that a structured transition from domestic to international exhibitions, supported by institutional facilitation and MSME preparedness, is essential to achieve sustainable and globally competitive MSME growth.